2015
DOI: 10.4149/av_2015_03_240
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic validation of recombinant hemagglutinin-neuraminidase protein of Newcastle disease virus expressed in Saccharomyces cerevisiae

Abstract: Summary. -The outer membrane glycoprotein, hemagglutinin-neuraminidase (HN) of Newcastle disease virus (NDV) is important for virus infection and subsequent immune response by host, and offers target for development of recombinant antigen-based immunoassays and subunit vaccines. In this study, the expression of HN protein of NDV is attempted in yeast expression system. Yeast offers eukaryotic environment for protein processing and posttranslational modifications like glycosylation, in addition to higher growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Using pESC-URA plasmid, SDH2-R32C and SNCA genes (synthesized by Kingsley Biotechnology Co., Ltd., China) were exogenously inserted and introduced into yeast cells for expression ( Khulape et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Using pESC-URA plasmid, SDH2-R32C and SNCA genes (synthesized by Kingsley Biotechnology Co., Ltd., China) were exogenously inserted and introduced into yeast cells for expression ( Khulape et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…with Salmonella flagellin as adjuvant. Khulape et al (2015) attempted to express the HN protein of NDV in a yeast expression system. The authors found that Saccharomyces cerevisiae was a better expression system for HN protein than Pichia pastoris as determined by codon usage analysis.…”
Section: Introductionmentioning
confidence: 99%